K2O 55 DISTRIBUTION ANOMALY OF VOLCANO IN JAVA ISLAND AND THE CORRELATION WITH JAVA ISLAND TECTONIC - Kurniawan, Oki
Java Island is one of the islands that has the most volcanoes in Indonesia with an interesting tectonic setting to study. The geochemical analysis of volcanoes on the island of Java is expected to improve the tectonic maps that have been around to date so that they can be of good use to explore resources and to anticipate disasters. The objects of this study were 460 geochemical data from 27 Quaternary volcanoes on the Java Island including Salak, Gede, Tangkuban Parahu, Patuha, Wayang Windu, Guntur, Papandayan, Cikuray, Galunggung, Telaga Bodas, Ciremai, Slamet, Dieng, Sundoro, Merbabu, Merapi, Muria, Lasem, Lawu, Wilis, Kelud, Bawean, Bromo, Lamongan, Argopuro, and Ijen. The data used in this study consisted of volcanic major element geochemistry, depth of Benioff Zone data, and Java regional tectonic data. The methodology used includes analysis of major elements especially K2O to obtain distribution maps and geochemical anomaly maps of Java Island which are then integrated with Benioff Zone data and regional tectonic data so that an interpretation of regional geochemical anomalies in Java is obtained. The K2O value is normalized against SiO2 with a value of 55 which aims to equalize the geochemical rock conditions so that the K2O data value distribution of the observed volcanoes can be comparable. The SiO2 value of 55 is used because the distribution of SiO2 data values on volcanoes in Java is generally classified into basaltic andesite so the value of 55 is considered to be able to represent the distribution of data on volcanoes in Java. Volcanic magma affinity in this study is generally included in the calc-alkaline series which may be related to the tectonic setting of the active continental margin. The results of the distribution of K2O values on SiO2 55 from each volcano show a spatial distribution that has several anomalies. These anomalies include the K2O value between Papandayan and Cikuray, between Merapi and Merbabu, between Muria and Lasem, and volcanoes in East Java, especially Raung and Ijen. These anomalie is then integrated with the Benioff Zone and regional tectonics to interpret the cause of the anomaly.The anomaly occurs in Papandayan-Cikuray is interpreted as the position of the two volcanoes is above the continuity of the Gondwana Fragment. The anomaly occurs in Merapi-Merbabu is interpreted as the location of Merapi above the continuity of the Gondwana Fragment while Merbabu is located above the Cretaceous Melange. The anomaly occurs in Lasem-Muria was interpreted as the existence of oceanic plate slab tear under Muria that caused a rise in the mantle which affecting Muria’s volcanism resulting in Muria's K2O value being much higher than Lasem. Anomalies that occur in volcanoes in East Java, especially Raung-Ijen, are interpreted to be caused by the presence of the Gondwana Fragment, in which its spatial boundary is located northward towards the modern volcanic arc in East Java. From the conclusions of the anomalies found, a tectonic map with changes in the spatial distribution of the Gondwana Fragment can be proposed. However, this proposal needs to be validated by carrying out further analysis such as a more detailed geochemical analysis of the major element volcanoes, a more complete analysis of trace elements, and an isotope analysis of each volcano.